Heat Shock-Induced Accumulation of the Glycogen Synthase Kinase 3-Like Kinase BRASSINOSTEROID INSENSITIVE 2 Promotes Early Flowering but Reduces Thermotolerance in Arabidopsis - Ren, Huimin; Wu, Xuedan; Zhao, Weishuang; Wang, Yuetian; Sun, Daye; Gao, Kang; Tang, Wenqiang (Frontiers in Plant Science, 2022)
Brassinosteroids (BRs) are essential plant growth- and development-regulating phytohormones. When applied exogenously, BRs ameliorate heat shock (HS)-induced cell damage and enhance plant thermotolerance; however, the molecular mechanism by which BRs regulate plant thermotolerance is unknown. In this study, by analyzing the thermotolerance of a series of BR signaling mutants and plants that overexpressed different BR signaling components, we obtained comprehensive data showing that BRASSINOSTEROID INSENSITIVE 2 (BIN2) plays a major role in mediating the crosstalk between BR signaling and plant HS responses. By RNA-Seq, 608 HS- and BIN2-regulated genes were identified. An analysis of the 1-kb promoter sequences of these genes showed enrichment of an ABA INSENSITIVE 5 (ABI5)-binding cis-element. Physiological studies showed that thermotolerance was reduced in bin2-1 mutant and ABI5-OX plants but increased in the abi5 mutant, and that the abi5 mutation could recover the thermotolerance of bin2-1 plants to a wild-type level, suggesting that ABI5 functions downstream of BIN2 in regulating plant thermotolerance. Further, HS treatment increased the cellular abundance of BIN2. Both bin2-1 mutant and BIN2-OX plants showed early flowering, while the BIN2 loss-of-function mutant bin2-3 bil1 bil2 flowered late. Given these findings, we propose that under HS conditions plants increase BIN2 activity to promote early flowering and ensure species survival; however, this reduces the thermotolerance and survivability of individual plants partially by activating ABI5.